2004
DOI: 10.1007/s00330-004-2589-5
|View full text |Cite
|
Sign up to set email alerts
|

3.0-T high-field magnetic resonance imaging of the female pelvis: preliminary experiences

Abstract: The purpose of this study was to evaluate if 3.0 T allows for clinically useful pelvic magnetic resonance imaging, i.e. if familiar image quality and tissue contrast can be achieved at 3.0 T as compared with at 1.5 T. Adapting a 1.5-T protocol to the 3.0-T environment is subject to a variety of factors. In order to reduce the number of potential variables, we chose two cornerstones: the 3.0-T sequence should have similar spatial resolution and acquisition time; furthermore, the contrast parameters repetition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 18 publications
1
28
0
2
Order By: Relevance
“…Although optimal parameters for imaging may differ between 3.0 T and 1.5 T, many radiologists use the same parameters for both (14). The MR signal intensity (S) for spin-echo sequence is generally obtained with the following equation:…”
Section: T Mri Of the Abdomen And Pelvis In Clinical Settingsmentioning
confidence: 99%
“…Although optimal parameters for imaging may differ between 3.0 T and 1.5 T, many radiologists use the same parameters for both (14). The MR signal intensity (S) for spin-echo sequence is generally obtained with the following equation:…”
Section: T Mri Of the Abdomen And Pelvis In Clinical Settingsmentioning
confidence: 99%
“…Morakkabati-Spitz and associates observed equiva- lent image quality between 1.5-and 3T MR images of the pelvis and found that choosing comparable parameters at 3T to those for 1.5T MR imaging maintained the familiar tissue contrast of the pelvic anatomy. 15 Recently, the clinical use of MR imaging at 3T has increased for female pelvic lesions. Hori and colleagues reported that 3 and 1.5T MR imaging are comparable for presurgical evaluation of patients with cervical cancer, 16 and Torricelli's team reported comparably high diagnostic accuracy of MR imaging at 3 and 1.5T in evaluating the depth of myometrial inˆltration of endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The GM and WM of the bilateral frontal lobes were selected as ROIs in each MR image. In each subject, we manually drew 5 ROIs, each of which contained an area of 16 pixels, in the same manner as we used in measuring relaxation time.…”
Section: -Flair Imagesmentioning
confidence: 99%